Different receptors mediating the inhibitory action of exogenous ATP and endogenously released purines on guinea-pig intestinal peristalsis - Heinemann, Ákos (1999)
1. Adenosine 5′-triphosphate (ATP) is an enteric neurotransmitter which acts at purine receptors on intestinal nerve and muscle. This study set out to shed light on the receptor mechanisms by which exogenous and endogenous ATP influences intestinal peristalsis. 2. Peristalsis in isolated segments of the guinea-pig small intestine was triggered by a perfusion-induced rise of the intraluminal pressure. Motor changes were quantified by alterations of the peristaltic pressure threshold (PPT) at which propulsive muscle contractions were elicited. 3. ATP (⩾3 μM) increased PPT and abolished peristalsis at concentrations of 100–300 μM. Adenosine 5′-O-2-thiodiphosphate (ADPβS, 3–100 μM) was more potent, whereas α,β-methylene ATP (α,β-meATP, 3–100 μM) was less potent, than ATP in depressing peristalsis. 4. 8-Phenyltheophylline (10 μM) attenuated the anti-peristaltic effect of 10 and 30 μM ATP but not that of higher ATP concentrations. Apamin (0.5 μM) counteracted the ability of ATP, ADPβS and α,β-meATP to enhance PPT. Suramin (300 μM) and pyridoxal phosphate-6-azophenyl-2′,4′-disulphonic acid (PPADS, 150 μM) antagonized the inhibitory effect of α,β-meATP on peristalsis but did not alter the effect of ATP and ADPβS. 5. PPADS (50–150 μM) reduced PPT by as much as 50%. This stimulant effect on peristalsis was prevented by suramin (300 μM) but left unaltered by apamin (0.5 μM) and N(G)-nitro-L-arginine methyl ester (300 μM). 6. These data show that exogenous and endogenous ATP inhibits intestinal peristalsis via different apamin-sensitive purinoceptor mechanisms. Exogenous ATP depresses peristalsis mostly via suramin- and PPADS-insensitive P2 receptors, whereas endogenous purines act via P2 receptors sensitive to both suramin and PPADS.